Design and performance evaluation of a low-cost Root Vegetable washing and peeling Machine - Neupane, Sudan; Gyawali, Anishma; Maharjan, Ayush; Khadka, Kritika; Maharjan, Salina (Journal of Innovations in Engineering Education, 2025)
This study presents the design and performance evaluation of a low-cost, small-scale mechanical system for simultaneous washing and peeling of root vegetables, with ginger and potatoes as test materials. The machine integrates a horizontally rotating drum lined with compression springs and an internal nozzle array to provide combined abrasive and hydraulic action. Performance tests were conducted at two drum speeds (25 rpm and 60 rpm) and two batch sizes (2.1 kg and 5 kg). Results indicate that operation at 25 rpm yields superior performance, achieving approximately 80% washing and peeling effectiveness with minimal flesh loss (2.05% for ginger and 2.25% for potatoes). Energy consumption was measured at 0.92 kWh per 60 s cycle, and the total fabrication cost was approximately USD 240, which is significantly lower than comparable commercial systems. The compact footprint (